Assessment of the structural validity of the domestic violence healthcare providers’ survey questionnaire using a Nigerian sample - John, Ime A (Kermanshah University of Medical Sciences, 2010)
BACKGROUND: There has been increased advocacy to involve healthcare providers in the prevention of intimate partner violence (IPV) through screening for it in healthcare. Yet, only one in ten providers screen for IPV, suggesting barriers. Understanding the readiness of healthcare providers to screen for IPV is therefore paramount. The Domestic Violence Healthcare Provider Survey Scales (DVHPSS) is a previously validated, comprehensive scale to study readiness of healthcare providers to screen for IPV. However, an understanding of its usefulness in the Sub-Saharan African context remains elusive. The current study undertook to examine the structural validity of the DVHPSS in Nigeria. METHODS: Exploratory factor analysis and Cronbach's Alpha were run to reveal the factorial structure and reliability of the instrument/subscales respectively. Established thresholds were used to determine significant factor loadings and alphas coefficient. RESULTS: A six factor model emerged, with 2 factors similar to the original scale, another two differing slightly and a further two factors resulting from a splitting up of the original combination of victim/provider safety to having distinct victim and provider safety subscales. CONCLUSIONS: With slight modifications, the DVHPSS can be use to study IPV screening among Nigerian healthcare professionals. Introducing screening protocols could promote better understanding of crucial questions that were lost in the analysis.